2015
DOI: 10.1039/c5cp01629k
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnCo2O4 nanoflakes grown on nickel foam as electrodes for high performance supercapacitors

Abstract: ZnCo2O4 nanoflakes, as electrodes for supercapacitors, are grown on a cellular nickel foam using a cost-effective hydrothermal procedure. The mesoporous ZnCo2O4 nanoflakes have large electroactive surface areas with strong adhesion to the Ni foam, allowing fast ion and electron transport. The nanoarchitecture electrodes deliver an excellent specific capacitance of 1220 F g(-1) at a current density of 2 A g(-1) in a 2 M KOH aqueous solution and a long-term cyclic stability of 94.2% capacitance retention after 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(36 citation statements)
references
References 44 publications
(43 reference statements)
2
34
0
Order By: Relevance
“…It is found that the electrode before cycling test has a more vertical straight line, demonstrating a lower Warburg resistance representing the ion diffusion of the electrolyte into the electrode surface . The electrode after 3000 cycles has an obvious bigger semicircle, which means a higher charge‐transfer resistance on the electrode surface . While the intersection of the curve at Z′ axis is equal to internal resistances which represent the bulk resistance of the electrochemical system.…”
Section: Resultsmentioning
confidence: 97%
“…It is found that the electrode before cycling test has a more vertical straight line, demonstrating a lower Warburg resistance representing the ion diffusion of the electrolyte into the electrode surface . The electrode after 3000 cycles has an obvious bigger semicircle, which means a higher charge‐transfer resistance on the electrode surface . While the intersection of the curve at Z′ axis is equal to internal resistances which represent the bulk resistance of the electrochemical system.…”
Section: Resultsmentioning
confidence: 97%
“…19 Another example is ZnCo 2 O 4 nanoakes, which could deliver a specic capacitance up to 1220 F g À1 at 2 A g À1 , which was about 500 F g À1 higher than that of Co 3 O 4 under the same conditions. 20 MgCo 2 O 4 with a spinel structure stands out among a variety of BTMOs because of its high theoretical specic capacitance ($3122 F g À1 ) and other good electrochemical properties. In the MgCo 2 O 4 crystal structure, the Mg cation occupies the tetrahedral site and the Co cation occupies the octahedral site.…”
Section: Introductionmentioning
confidence: 99%
“…ZnCo 2 O 4 (ZCO) has been promoted as an electrode material for energy storage devices due to its high theoretical capacitance, electrical conductance, enhanced cycle stability, abundant resources and low price [ 25 , 26 , 27 ]. Recently, ZCO has been studied for Li-ion batteries and photocatalytic CO 2 reduction [ 28 , 29 ]. ZCO materials have been prepared with various morphologies such as nanosheets, nanorods, nanotubes, nanowires and nanoparticles [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%